Turismo cultural y desarrollo sostenible en el cantón Guano, provincia de Chimborazo - López Guapi, Allison Nicole (2025)
This research examines the relationship between cultural tourism and sustainable development in Guano Canton, located in the Chimborazo Province of Ecuador. The study addresses challenges such as inadequate management of cultural tourism, insufficient tourism promotion, limited community involvement, and substandard infrastructure and services—factors that hinder the sustainable development of tourism in the region. The primary objective is to assess how cultural tourism can contribute to sustainable development by preserving cultural heritage, enhancing the quality of life for local residents, and strengthening the canton’s economy. The methodology combined both documentary analysis and field research. A comprehensive literature review on cultural tourism and sustainable development was conducted, complemented by on-site data collection in Guano Canton. The research design was non-experimental, as no variables were manipulated, and descriptive in nature, enabling the identification of key dimensions and indicators. Furthermore, it employed a correlational approach to assess the relationship between cultural tourism and sustainable development, and it was cross-sectional, with data collected at a single point in time. The findings reveal a direct and significant relationship between cultural tourism and sustainable development, as evidenced by a correlation coefficient of 1.000, indicating a perfect positive association. These results highlight the need for effective tourism management strategies that foster community participation and enhance infrastructure, thereby supporting balanced and sustainable development in Guano Canton.